SHORT-LIVED PLAY : Trans-European travels in print sex edutainment - Paasonen Susanna; Saarenmaa Laura Ellen (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
Media history is still written largely from national perspectives so that the role of import and export, translations and franchises is seldom foregrounded. On geographically and linguistically limited markets, imported materials have nevertheless been crucial parts of popular print culture. This paper explores the market of 'sex edutainment' magazines in 1970s Finland, zooming specifically in on Leikki ('Play', 1976), a sex magazine for women translated from the Norwegian Lek (first launched in 1971) that provided knowledge on topics ranging from marriage to masturbation and lesbian desire. Through contextual analysis of Leikki, a marginal publication that has basically faded from popular memory, this article attends to ephemeral and even failed print media in order to account for the heterogeneity of the 1970s sex press market as it intermeshed with sex advice and education. In so doing, it adds new perspectives to a field largely focused on successful periodicals and addresses knowledge gaps resulting from the exclusion of the sex press from mainstream media historiography.